Pengaruh Lingkungan Kerja Terhadap Kinerja Tenaga Kependidikan di Akademi Maritim Cirebon - Fereddy Siagian (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
The purpose of this study is to analyze the effect of the work environment on the performance of the educational staffs. The method used in this study was a quantitative descriptive study with a total sample of 51 respondents. The sampling technique used probability sampling method with simple random sampling technique. The instrument testing used a validity test and a reliability test. Data analysis used simple linear regression analysis with t test and coefficient of determination test. The results of the study showed that the work environment was very influential on the performance of educational staffs within the scope of the AMC office. Conducive work environment provided maximum performance of all teaching staffs.